Summer schools of adult and paediatric respiratory medicine: course report. Issue 4 (December 2016) - Horvath, Ildiko; Kovacs, Gabor; Munteanu, Oxana; Kmyta, Vladyslava; Midulla, Fabio; Kadam, Shashank; Rumman, Nisreen
The ERS summer schools in both adult and paediatric respiratory medicine were held in Lisbon, Portugal on June 15–18, 2016. The summer schools provide a comprehensive update on adult/paediatric respiratory medicine and are intended to help participants prepare for the European examination in adult/paediatric respiratory medicine. The course programmes are designed to challenge participants and each course included a mixture of case presentations with interactive discussions, plenary lectures and workshops. ERS hosted summer schools on adult and paediatric respiratory medicine in Lisbon, Portugal http://ow.ly/qcas304C5tO